A combined risk analysis approach for complex dam–levee systems. Issue 12 (2nd December 2017) - Castillo-Rodríguez, Jesica Tamara; Needham, Jason T.; Morales-Torres, Adrián; Escuder-Bueno, Ignacio
Abstract: In many areas of the world, dams and levees are built to reduce the likelihood of flooding. However, if they fail, the result can be catastrophic flooding beyond what would happen if they did not exist. Therefore, understanding the risk reduced by the dam or levee, as well as any risk imposed by these flood defences is of high importance when determining the appropriate risk reduction investment strategy. This paper describes an approach for quantifying and analysing risk for complex dam–levee systems, and its application to a real case study. The basis behind such approach rely on the potential of event tree modelling to analyse risk from multiple combinations of 'load-system response-consequence' events, tested by the authors for a real case study. The combined approach shows how the contribution to system risk of each sub-system can be assessed. It also describes how decisions on risk mitigation measures, at the individual asset scale, can and should be informed in terms of how they impact the overall system risk.